Efeito do extrato aquoso de sementes de nim sobre a mosca-minadora em meloeiro - Carvalho, Adriano Soares de (2017)
The objectives of this work were: to evaluate the effect of different concentrations of the aqueous extract of neem seeds (Azadirachta indica); to analyze the action of this extract on the larval stages and to verify the residual effect of the extract on the mortality of the leafminer (Liriomyza sativae) in melon. The research was carried in Universidade Federal Rural do Semi-Árido, in Mossoró-RN. The study was divided in two experiments: on the first, the translaminar and systemic effect of aqueous extract of neem seeds on the larval instars of the leafminer in melon was analyzed through laboratory tests, where larval, pupal and total mortalities of L. sativae were calculated by spray and soil application of five concentrations of the neem seed extract (2, 5, 10, 15 and 20 g, 100 mL-1). We observed the effect of the extract, at the 5 g.100 mL-1 concentration, on the larval instars of L. sativae. We verified translaminar and systemic effect of aqueous extracts of neem seeds and Azamax® on larvae of L. sativae in melon, with the increase in mortality with the increase of extract concentration and high pupal and total mortality in both methods of application. The extract at the concentration of 5 g. 100 mL-1 caused significant mortality compared to control in both application methods and at all larval stages, but higher spray efficiency was obtained on larvae of the 1st instar. In the second experiment, the residual effect of the aqueous extract of neem seeds on the leafminer was analyzed in greenhouse conditions, using the two methods of application in the soil and sprayed on melon plants infested at different intervals of time after application (5, 7, 10, 15 and 20 days). The extract presented statistical difference of the control treatment in the two methods of application and all times of infestation. The spray application of the extract caused high larval and pupal mortality, besides low adult emergence, especially in plants infested up to seven days after application. In the other times, there was a gradual reduction in the effects of the extracts. The application of the soil extract caused a low larval mortality during the 20 days of the experiment, but caused high pupal mortality in infested plants only on the 5th day after the application, with reduction from 7th to 20th day. The results demonstrate that the aqueous extract of neem seeds causes significant mortality of larvae and pupae of L. sativae when sprayed on the leaves, with residual effect for 20 days, being more effective in the first seven days after application. The application of the aqueous extract of neem seeds via spraying showed higher rates of larval, pupal and lower emergence of adults when compared to application via soil in all times tested. We concluded that neem-based products have a translaminar and systemic effect on L. sativae mortality in melon plants, with an increase in mortality due to the increase in extract concentrations, and although there is considerable larval mortality, effects on mortality were higher in the pupal phase. We also observed higher efficiency of neem seed extract in L. sativae mortality at concentrations higher than 5 g. 100 mL-1. In addition, the application of the spray extract causes a higher mortality rate than the soil application, especially when applied to young larvae of the 1st instar and reduces in applications on more developed larvae. On the other hand, the spraying of the extract at a concentration of 5 g. 100 mL-1 had a residual effect on mortality for 20 days after application, but in soil application it presented low mortality in the same period